The Effect of Tallow As Lipase Inducer on Total of Aspergillus Niger, Lipolitic Activity and Lipase Yield (Jurnal Ilmu dan Teknologi Hasil Ternak, 2011)
The objectives of this research was to determined of tallow addition with different concentration as lipase Aspergillus niger inducer to total of A. niger, lipolitic activity and lipase yield. The result showed that tallow addition as inducer in the lipase A. niger production gave no significant effect on total of A. niger (5.3 x 107 – 1.7 x 108 cfu/gram) in the medium. Tallow addition gave a highly significant effect on lipolytic activity and yield of lipase A. niger. Lipolytic activity ranged between 32.0354 – 53.1197 U/mg protein, while the yield of lipase was 6.6418–7.8941 µg/ml. The conclusion of this research was the addition of tallow for 8% as the lipase inducer of A. niger on lipase production was  more effective to obtain the optimal result. Keywords : Tallow, lipase, inducer, Aspergillus niger